2012
DOI: 10.1093/nar/gks750
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 inhibits Schwann cell proliferation and migration by targeting FGF9 and NTM, respectively at an early stage following sciatic nerve injury

Abstract: The regulation of Schwann cell (SC) responses to injury stimuli by microRNAs (miRNAs) remains to be explored. Here, we identified 17 miRNAs that showed dynamic expression alterations at five early time points following rat sciatic nerve resection. Then we analyzed the expression pattern of 17 miRNAs, and integrated their putative targets with differentially expressed mRNAs. The resulting 222 potential targets were mainly involved in cell phenotype modulation, including immune response, cell death and cell loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 37 publications
1
90
0
Order By: Relevance
“…All animal experiments were carried out in accordance with the institutional animal care guidelines of Nantong University and approved by the Administration Committee of Experimental Animals, Jiangsu Province. A total of 72 rats underwent surgery for sciatic nerve transection as described previously (21). The TA muscle was harvested from a cohort of rats at 0, 3, 7 and 14 days postsurgery.…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments were carried out in accordance with the institutional animal care guidelines of Nantong University and approved by the Administration Committee of Experimental Animals, Jiangsu Province. A total of 72 rats underwent surgery for sciatic nerve transection as described previously (21). The TA muscle was harvested from a cohort of rats at 0, 3, 7 and 14 days postsurgery.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Migration Assay-Migration of oligodendrocyte Gsn3 was studied using 6.5-mm Transwell chambers with 8-m pores (Corning Costar) as described previously (50). 100 l of oligodendrocytes (2 ϫ 10 5 cells/ml) resuspended in DMEM/ F-12 were transferred to the top chambers of each transwell and allowed to migrate at 30°C in 5% CO 2 for 36 h, and 600 l of DMEM/F-12 including 1 g/ml recombinant proteins or antibodies (1:50) was injected into the lower chambers.…”
Section: Surveys Of Hmgb1 Paralogs Inmentioning
confidence: 99%
“…In the PNS, mature miRNAs are critical for SC differentiation and myelination [9,10]. Our previous studies have also shown that several miRNAs, including miR-221/222, miR-182, and miR-9, are involved in phenotype modulation of SCs after sciatic never injury [11][12][13].…”
Section: Introductionmentioning
confidence: 97%